Implementasi Profil Pelajar Pancasila Dalam Pembelajaran PAI dan Budi Pekerti Berbasis Merdeka Belajar - Nurhantara, Yulian Rizky; Ratnasari Dyah Utami (Jurnal Elementaria Edukasia, 2023)
Education is an effort to mature students, both mentally and in thinking. Through the learning process, students are directed, guided, fostered, explored, and develop their potential to reach maturity. Therefore, this study aims to see how implementing the Pancasila Student Profile in PAI and Moral learning is based on the “Merdeka Belajar”. This research uses qualitative and descriptive approaches. The data collection techniques used are interviews, observation, and documentation. Test the validity of the data using source triangulation techniques and method triangulation. Data analysis techniques in this study use data reduction, data presentation and conclusion drawing. The results of the research carried out, namely in the application of the Pancasila Student Profile at SD Negeri 03 Bejen Karanganyar, have been maximized because all indicators of the Pancasila Student Profile are met, even though the Global Diversity indicator is obtained through learning Civic Education (Civics) and through the habit of singing the Indonesian national anthem every morning before starting learning. Implementing the Pancasila Student Profile as a manifestation of character education requires all parties, from school principals, teachers, and parents to help.